The Use of “Power Pose” in English Class Interaction in Grade IX of MTs N 2 Medan - Rizky Ananda; Sumarsih Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
Ananda, Rizky. Registration Number: 2183321053. The Use of “Power Pose” in English Class Interaction in Grade IX MTsN 2 Medan. A Thesis. English Educational Program, Faculty Languages and Arts, Universitas Negeri Medan 2022. This study focuses on the level of student anxiety, student anxiety factors, and the use of power poses in class IX-10 MTs Negeri 2 Medan. In this study, the researcher used a qualitative descriptive research design to investigate the level and factors of students' anxiety and the use of power poses in the classroom. Cuddy (2010) states that a human's actions are influenced by the body pose he uses and that is why Cuddy coined his statement as a Power Pose. Power Pose is divided into 2, namely: high power pose and low power pose. The study took a sample of 30 students who were in class IX-10 MTsN 2 Medan. This study was conducted at the same time to see whether there is a relationship between power pose and anxiety level in students at MTsN 2 Medan. Data collection techniques used a questionnaire, observation, and documentation with pictures of the class situation 2 minutes before the teacher came and started the lesson as well as notes about the body poses of students and students who answered the teacher's initiation. The findings state that the average student is in the "anxious" level with a score of 109 with anxiety factors: 1) lack of confidence, 2) fear of making mistakes, 3) not understanding what the teacher says, 4) panic if ordered by the teacher to respond suddenly (without preparation), and 5) insecure about the ability of friends who are considered better. This is what makes this class less responsive to the teacher. And in this finding it was found that only 8 students used power poses (27%) while the remaining 22 students (73%) used low power poses.Keywords: Students’ Anxiety, Level Anxiety, Factor Anxiety, Classroom Interaction, Power Pose